Latin America: Knowledge diversity for a sustainable future. (15th February 2023) - Chiang, Gustavo; Umbuzeiro, Gisela; Lo Nostro, Fabiana
Abstract: National and international collaboration and the incorporation of perspectives from outside academia are essential parts of a paradigm shift in science and are necessary for a sustainable future. The articles in this special series "Diversity of Knowledge for a Sustainable Future in Latin America" exemplify many of these aspects, showcasing the latest research and environmental policies for the protection of water, soil, and human health related to several pollutants, for example, microplastics, hydrocarbons, metals, and pesticides. Knowledge—built in an environment where communities are participants in this construction and not only subjects—helps promote understanding of the transdisciplinary nature of environmental issues provided by a diversity of traditional and nontraditional participants. Integr Environ Assess Manag 2023;19:613–614. © 2023 SETAC